Eaton mobile hydraulics manual. (Eden Prairie : Eaton, 2006)
This edition has improved graphics; we've expanded some of the chapters; we've added questions to the end of each chapter; and added more topics. The latest addition to our textbook collection, is the 2nd edition of the Mobile Hydraulics Manual. It is hardbound with over 500 pages and 475 illustrations. Every major aspect of mobile hydraulics theory and application is covered, including: basic hydraulic theory, basic electrical theory, hydrostatic transmissions, steering and fixed and variable diplacement pumps.
Keywords: Hydraulica